Human dominion and wild animal suffering. Issue 4 (December 2022) - Crummett, Dustin
Abstract: It may be possible, now or in the future, for humans to technologically intervene to reduce the amount of suffering experienced by wild animals. There is a debate about whether, if humans can do this, they should. Here, I consider the implications for this debate of the theological claim that humans have been granted dominion over the other animals. I argue that it's more plausible to interpret the dominion claim as granting humans (i) the responsibility to care for the well-being of individual animals than to interpret it as giving humans either (ii) the right to do whatever they want to other animals or (iii) the responsibility to care only for the well-being of aggregates of animals (such as whole species). I then show how this understanding of dominion undermines a range of arguments against intervening to reduce wild animal suffering. These arguments claim that humans do not stand in the right sort of relationship for intervention to be obligatory (or perhaps even permissible). But if we possess such dominion, we do stand in the right sort of relationship for it to be obligatory.